Slov'jans'ko-shidnoromans'ka vzajemodija v gidronimii basejnu Dnistra - Verbyč, Sv'atoslav Oleksijovyč (Linguistica (Ljubljana), 2015)
The article describes Slavic and Eastern Romance language contact in the Dniester river basin. We investigate the etymology of the hydronyms that have Eastern Romance (Romanian and Moldavian) language elements in their structure. We analzse how water bodies' names (Slavic and Turkic) were adapted in the Eastern Romance linguistic system. It should be stressed that the number of Eastern Romance names as well as names which were adapted to Eastern Romance in the composition of hydronymy the Dniester river basin is insignificant (about 150). The chronological boundary of the formation of these names in the Carpathian part of the Dniester basin is the period from the thirteenth to the eighteenth centuries and the fourteenth to the eighteenth centuries for the area between the Prut and the Lower Dniester.
Keywords: Dnester (reka); etimologija; étymologie; etymology; geografska imena; hydronymes; langues romaines; langues slaves; romanski jeziki; Slavic languages; slovanski jeziki; toponymes; vodna imena